Pellet quality affects growth performance of nursery and finishing pigs - Stark, C.R.; Hines, Robert H.; Behnke, Keith C.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two experiments were conducted to determine the effects of diet form (meal vs pellet) and amount of fines in pelleted feed on growth performance of nursery and finishing pigs. One hundred twenty-six weanling pigs, with an average initial body wt of 12.5 lb, were used in the 35-d nursery experiment. The same phase I diet (pelleted) was fed to all pigs for 7 d, then the pigs were switched to phase II diet treatments (d 7 to 35 postweaning). Treatments were the same phase II diet fed as: 1) meal; 2) screened pellets (fines removed); and 3) the screened pellets with 25% added fines. From d 7 to 21, average daily gain (ADG) tended to be greater for pigs fed pellets, and feed/gain (F/G) was improved by 14% when pigs were fed pelleted diets compared with those fed the meal diet. Also, pigs fed the screened pellets had a 7% improvement in F/G compared to pigs fed the pelleted diet with 25% fines. From d 7 to 35, pigs fed pelleted diets were 9% more efficient than pigs fed the meal diet. Also, pigs fed the pelleted diet with 25% added fines had 2.6% poorer F/G than pigs fed the diet with screened pellets. In the finishing experiment, 80 gilts (average initial body wt of 118 lb) were used to evaluate the effects of diet form and pellet fines on growth performance. Treatments were a common finishing diet fed as: 1) meal; 2) screened pellets; 3) pellets with 20% fines; 4) pellets with 40% fines; and 5) pellets with 60% fines. Pigs fed the meal diet or the diet with 60% fines tended to have decreased ADG compared to pigs fed the other pelleted diets. Pigs fed screened pellets had a 4.7% improvement in F/G compared with those fed the meal diet. However, increasing the amount of fines in the screened pellets diet resulted in a linear trend for poorer F/G. These results suggest that pelleting diets improved growth performance in nursery and finishing pigs; however, increasing amounts of pellet fines reduced the advantage of feeding a pelleted diet.
Keywords: Swine; Nursery; Finishing; Pellets; Process